Perkembangan Ekonomi Pedagang Setelah Dibangunnya Pasar Angso Duo Baru Jambi - Feni Agustiani; Azmi Fitrisia (Jurnal Kronologi, 2021)
Abstract This study aims to determine the economic development of traders after the construction of the new Angso Duo market in Jambi.the focus this research is from 2014 to 2021 the method used in this research is the historical method which consists of four stages namely heuristics, source criticism, interpretation, and historiography. Based on the result of the research that in 2014 one of the markets in the city of Jambi was built, namely the Angso Duo Baru market, Jambi which is managed PT. Eraguna Bumi Nusa in collaboration with the Jambi City Government, finally this market was completed in 2018 into a traditional market with modern nuances and market facilities are quite good. After the construction of the new Angso Duo market, it was able to increase the income of the Jambi. In addition, the impact felt by traders and buyers with the existence of a impact felt by traders and buyers with the existence of a market building that has provided comfort and security, the pysical condition of thr market greatly affects the income of traders and the region.